Brain-Stem Evoked Potentials and their Generations - Simhadri, Radha (Journal of All India Institute of Speech and Hearing)
Evoked potentials in response to auditory stimuli have been studied for many years. Fifteen individual potential wave-forms can be identified in the averaged responses (Picton et al., 1974). Due to technological reasons, it is only since a decade that attention has been turned to study the early portion of the evoked response (waves having latencies less than 10m. Sees). This sequence of waves which are separated by intervals of approximately lm. Sec. have been tentatively correlated with activation of the brain-stem auditory nuclei and thus have been termed the Brain-stem Evoked Responses (BSER). This BSER could provide a sensitive and objective audio logical and neurological measure which would be particularly useful among populations unable to respond appropriately in con- ventional auditory testing.